A test of the automaticity assumption of compliance tactics: discouraging undergraduate binge drinking by appealing to consistency and reciprocity - Conner, Amy E.; Miller, Megan M.; Brannon, Laura A. (My University, 2014)
The mindfulness of compliance with requests making use of the commitment/consistency or the reciprocity principle was investigated. Participants (N = 129) received a foot-in-the-door (FITD) request (commitment/consistency application), a door-in-the-face (DITF) request (reciprocity application), or no request. Next, participants read either a weak or neutral message about the importance of moderate alcohol consumption then reported the likelihood of not drinking excessively for one week (target request). When accompanied by a weak message, the target request elicited less compliance if preceded by the DITF or FITD requests than by no initial request, suggesting compliance tactics sometimes increase thoughtfulness.
Keywords: Compliance; Automaticity; Binge drinking; Mindfulness